Involuntary consent - Futter, Dylan Brian (Rhodes University, Faculty of Humanities, Department of Philosophy)
In this dissertation I take exception with a widely held philosophical doctrine, according to which agents are only blameworthy for the bad actions they have chosen to bring about. My argument strategy is to present cases in which agents are blamed for involuntary actions that are not in any way connected to their culpable and voluntary choices. These failures correspond, I suggest, to occasions of culpable ignorance where agents have been negligent or careless. More specifically, I claim that violations of natural duties of respect and consideration, and certain acquired role-type duties, are blamed without any voluntary consent. If my examples are persuasive, then the point is reached where a normative principle of 'voluntary consent' does not in fact coincide with people's actual practices and 'considered judgements'. In the final sections of the dissertation, I argue against the plausibility of keeping the principle and revising our judgements.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Ignorance (Theory of knowledge); Responsiblity; Free will and determinism; Theory (Philosophy); Social ethics; Blame